2014
DOI: 10.1017/s1049023x14000636
|View full text |Cite
|
Sign up to set email alerts
|

Medical Support at a Large-scale Motorsports Mass-gathering Event: The Inaugural Formula One United States Grand Prix in Austin, Texas

Abstract: This mass-gathering motorsport event had a moderate number of patients requiring medical attention. The preparedness plan was implemented successfully with minimal impact on EMS resources and local medical facilities. This medical preparedness plan may serve as a model to other cities preparing for an inaugural motorsports event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The need for authorities to prepare for mass gatherings with sufficient resources and the need for preparedness for non-organized events, such as nationwide celebrations after major sports wins or end of school celebrations in May also stood out from the results. Previous research shows that mass gatherings may especially strain resources of the EMS, healthcare facilities, and police forces, and they require pre-planning [8,12,37,40]. The results of this study further showed that pre-checking of the arrangements ensures the actualization of the emergency plan and event organizer's competence for risk identification.…”
Section: Co-operation In the Pre-planning Phasesupporting
confidence: 51%
See 1 more Smart Citation
“…The need for authorities to prepare for mass gatherings with sufficient resources and the need for preparedness for non-organized events, such as nationwide celebrations after major sports wins or end of school celebrations in May also stood out from the results. Previous research shows that mass gatherings may especially strain resources of the EMS, healthcare facilities, and police forces, and they require pre-planning [8,12,37,40]. The results of this study further showed that pre-checking of the arrangements ensures the actualization of the emergency plan and event organizer's competence for risk identification.…”
Section: Co-operation In the Pre-planning Phasesupporting
confidence: 51%
“…Sufficient first-aid capability and the quality of security emerged from the results along with other needed services, such as taking care of water supply. Previous studies indicated that on-site medical staff should include health professionals along with first-aid providers [15,18,19,23,40]. According to Locoh-Donou et al [26], absence of free drinking water is strongly associated with patient presentations.…”
Section: Factors To Be Noted In the Emergency Planmentioning
confidence: 99%
“…Some work has been undertaken to predict patient presentations to hospital emergency departments/emergency rooms (ERs) from the general community population 34 35 However, predicting the patient presentations to ERs as a result of mass gatherings is not yet discussed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Current MGM literature consists mainly of descriptive case studies of specific individual events. [5][6][7][8][9][10][11] In this analysis, we investigate variation between patient presentations and ambulance transport rates across various event types, as well as the reasons for seeking medical care. We present our experience managing >200 mass gathering events of various types over a 6-year period at Gillette Stadium.…”
Section: Importancementioning
confidence: 99%